АНАЛИЗ ДИНАМИКИ БЕЗРАБОТИЦЫ И ТЕНЕВОЙ ЭКОНОМИКИ В УСЛОВИЯХ РЫНОЧНЫХ ОТНОШЕНИЙ (Journal of Economic Research & Business Administration, 2016)
The article provides with analysis of unemployment rate dynamics in countries with market economy including Republic of Kazakhstan, and shady economy as factors of economical instability of Republic’s development. Recommendations concerning decrease of their negative impact on domestic economy are given.